A Photoactive Supramolecular Complex Targeting PD-L1 Reveals a Weak Correlation between Photoactivation Efficiency and Receptor Expression Levels in Non-Small-Cell Lung Cancer Tumor Models - Pietro Delcanale; Manuela Maria Alampi; Andrea Mussini; Claudia Fumarola; Maricla Galetti; Pier Giorgio Petronini; Cristiano Viappiani; Stefano Bruno; Stefania Abbruzzetti (MDPI AG, 2023)
Photo-immunotherapy uses antibodies conjugated to photosensitizers to produce nanostructured constructs endowed with targeting properties and photo-inactivation capabilities towards tumor cells. The superficial receptor density on cancer cells is considered a determining factor for the efficacy of the photodynamic treatment. In this work, we propose the use of a photoactive conjugate that consists of the clinical grade PD-L1-binding monoclonal antibody Atezolizumab, covalently linked to either the well-known photosensitizer eosin or the fluorescent probe Alexa647. Using single-molecule localization microscopy (direct stochastic optical reconstruction microscopy, dSTORM), and an anti-PD-L1 monoclonal antibody labelled with Alexa647, we quantified the density of PD-L1 receptors exposed on the cell surface in two human non-small-cell lung cancer lines (H322 and A549) expressing PD-L1 to a different level. We then investigated if this value correlates with the effectiveness of the photodynamic treatment. The photodynamic treatment of H322 and A549 with the photo-immunoconjugate demonstrated its potential for PDT treatments, but the efficacy did not correlate with the PD-L1 expression levels. Our results provide additional evidence that receptor density does not determine a priori the level of photo-induced cell death.